Music and Visual Culture in Renaissance Italy - Henry, Chriscinda; Shephard, Tim (Taylor & Francis, 2023)
The chapters in this volume explore the relationship between music and art in Italy across the long sixteenth century, considering an era when music-making was both a subject of Italian painting and a central metaphor in treatises on the arts. Beginning in the fifteenth century, transformations emerge in the depiction of music within visual arts, the conceptualization of music in ethics and poetics, and in the practice of musical harmony. This book brings together contributors from across musicology and art history to consider the trajectories of these changes and the connections between them, both in theory and in the practices of everyday life. In sixteen chapters, the contributors blend iconographic analysis with a wider range of approaches, investigate the discourse surrounding the arts, and draw on both social art history and the material turn in Renaissance studies. They address not only paintings and sculpture, but also a wide range of visual media and domestic objects, from instruments to tableware, to reveal a rich, varied, and sometimes tumultuous exchange among musical and visual arts and ideas. Enriching our understanding of the subtle intersections between visual, material, and musical arts across the long Renaissance, this book offers new insights for scholars of music, art, and cultural history.